The Oxford handbook of the Minor Prophets - O'Brien, Julia M. (Oxford handbooks online Religion, 2021)
The Oxford Handbook of the Minor Prophets provides a clear and engaging one-volume guide to the major interpretative questions currently engaging scholars of the twelve Minor Prophets. Essays by both established and emerging scholars explore a wide range of methodological perspectives. Historical studies consider the manuscript evidence for these books and overview debates about how, when, and by whom they were composed. Literary explorations consider the genres and rhetorical style of the material, key themes, and intertextual connections with other sections of the Jewish and Christian canons. A large section on the history of interpretation traces the ways in which past and present confessional communities, scholars, and artists have understood the Minor Prophets. In the final section, essays on individual books of the Twelve explore the structure, themes, and contested issues of each book.